2022
DOI: 10.26434/chemrxiv-2022-9b3s1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of Adagrasib’s Commercial Manufacturing Route

Abstract: A commercial route to MRTX849 (adagrasib) was developed to support clinical and commercial needs. Yield was improved to 32% over six chemical steps. A doubly regioselective SNAr reduced consumption of an expensive chiral intermediate, reaction optimization led to parts per million palladium catalysis, and a new method to deprotect Cbz-groups were developed to mitigate risk associated with benzyl iodide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…This publication communicates those efforts. 3 Commercial route development began with a review and analysis of adagrasib's reported route (Figure 2). 4 Iterative side-chain appendage to bicyclic pyrimidine core 2 resulted in modular synthesis, and preparation required a longest linear sequence (LLS) of 8 synthetic steps from building blocks.…”
Section: Reported Routementioning
confidence: 99%
“…This publication communicates those efforts. 3 Commercial route development began with a review and analysis of adagrasib's reported route (Figure 2). 4 Iterative side-chain appendage to bicyclic pyrimidine core 2 resulted in modular synthesis, and preparation required a longest linear sequence (LLS) of 8 synthetic steps from building blocks.…”
Section: Reported Routementioning
confidence: 99%
“…A unique 2-fluoroacrylamide warhead located at the distal side of the piperazine is responsible for covalent binding to the target protein. As shown in Scheme , the current synthetic route started with a Boc-protected tetrahydropyrido­pyrimidine 2 . A regioselective S N Ar reaction introduced the Cbz-masked piperazine moiety 3 at the more reactive 4-position.…”
mentioning
confidence: 99%
“…When the readily available 2-nitrobenzene­sulfonate was used (Scheme ), the telescoped activation-S N Ar process afforded product 9 in 90% yield and excellent purity . Finally, n -propane­phosphonic acid anhydride (T 3 P)-mediated amidation of 9 with 10 afforded adagrasib ( 1 ) in 85% yield. , It should be noted that using sodium acrylate 10 instead of the free acid minimized the decomposition of the acid and obviated the use of amine base in the T 3 P mediated coupling.…”
mentioning
confidence: 99%
See 2 more Smart Citations